Al-GHAZALIS EDUCATIONAL PHILOSHOPY FIGURE - Alvi Anaya; Azra Henita Hanin Nst (Proceeding International Seminar of Islamic Studies, 2022)
Philosohpy is a human activity in using his mind as well as possible, to know and answer in depth all problems. If all of these problems are oriented towards understanding the field of education, what is known as the philosophy of education is born. The philosophy of education is not general philosophy or a pure philosophy, but a special or applied philosophy. Philosophy of education is a type of knowledge that discussed all issues related to education, with a view to obtaining answer to be used as directions for the implementation and development of education. When islamic philosophy is discussed, it will be imagined Al-Ghazali where is figure is a figure in the philosophy of islamic education. He not only introduced islamic philosophy, but also developed philosophy itself. In this article, we will tell more about the figure of the philosophy of islamic education, namely Al-Ghazali.Keywords: Philosophy, Getting to Know Al-Ghazali's Philosophy Figures Deeper